When these things begin: conversations with Michel Treguer - Girard, René (Studies in violence, mimesis, and culture, 2014)
In this lively series of conversations with writer Michel Treguer, René Girard revisits the major concepts of mimetic theory and explores science, democracy, and the nature of God and freedom. Girard affirms that "our unprecedented present is incomprehensible without Christianity." Globalization has unified the world, yet civil war and terrorism persist despite free trade and economic growth. Because of mimetic desire and the rivalry it generates, asserts Girard, "whether we're talking about marriage, friendship, professional relationships, issues with neighbors or matters of national unity